2018
DOI: 10.1186/s13567-018-0605-z
|View full text |Cite
|
Sign up to set email alerts
|

Associations between digital dermatitis lesion grades in dairy cattle and the quantities of four Treponema species

Abstract: Digital dermatitis (DD) presents as painful, ulcerative or proliferative lesions that lead to bovine lameness affecting economic efficiency and animal welfare. Although DD etiological agent(s) have not been established, it is widely accepted that DD is a polymicrobial disease significantly associated with species of Treponema and the non-linear disease progression may be attributed to interactions among infecting bacteria. We postulated the morphological changes associated with DD lesion grades are related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 40 publications
2
40
0
Order By: Relevance
“…Positive cultures came from cases with M2, M3, M4 and M4.1 lesions. It has been shown that treponeme numbers are higher in active ulcerative lesions (as previously determined using qPCR to quantify bacterial DNA, rather than using culture) [16]. Our results indicate that higher percentages of M2, M3 and M4.1 lesions lead to positive cultures post-trimming when compared to the chronic M4 stage; however, this effect could be due to smaller sample sizes in the other lesion categories and overall insufficient sample size.…”
Section: Discussionmentioning
confidence: 44%
“…Positive cultures came from cases with M2, M3, M4 and M4.1 lesions. It has been shown that treponeme numbers are higher in active ulcerative lesions (as previously determined using qPCR to quantify bacterial DNA, rather than using culture) [16]. Our results indicate that higher percentages of M2, M3 and M4.1 lesions lead to positive cultures post-trimming when compared to the chronic M4 stage; however, this effect could be due to smaller sample sizes in the other lesion categories and overall insufficient sample size.…”
Section: Discussionmentioning
confidence: 44%
“…A species-specific qPCR assay [ 14 ] was used for in-tissue Treponema quantification. Clones targeting unique genes of Treponema pedis (CP004120), T. phagedenis (WP_002698807.1) and T. medium (WP_016523385.1) were generated and used for quantification.…”
Section: Methodsmentioning
confidence: 99%
“…are consistently identified in active bovine DD lesions [ 8 , 10 , 11 , 12 ], the exact role of these spirochetes in the aetiopathogenesis of DD remains unclear [ 13 ]. Treponema phagedenis , T. medium , T. pedis are among the most commonly detected species in DD lesions [ 8 , 10 , 11 , 14 , 15 ]. Interestingly, DD-associated treponemes have also been associated with other hoof-related animal diseases, including contagious ovine digital dermatitis [ 16 ] and elk hoof disease [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations